2021
DOI: 10.1155/2021/9980549
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Mechanical Properties of Freeze‐Thaw Damaged Red Sandstone under Combined Dynamic and Static Loading

Abstract: Using the freeze-thaw cycle test chamber, the red sandstone samples are subjected to cyclic freeze-thaw tests. The physical properties, static mechanical properties of freeze-thaw damage rocks, and the compressional wave velocity at specific axial pressure are measured using conventional physical tests and uniaxial compression tests. The mechanical properties of freeze-thaw damage rocks under dynamic and static loading were studied using Hopkinson pressure bar which can exert axial pressure. The studies show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…DCS of rocks was determined using Hopkinson separated compression rods, with confining pressure gradients of 0, 2, 5, and 10 MPa, and an impact pressure range of 0.2 to 0.6 MPa. This paper conducted intelligent prediction research based on ten influencing factors affecting the DCS of rocks under freeze-thaw cycles [28,[47][48][49][50][51] , including FTC, CP, IP, DD, NWC, WA, ADW, P, PWV, and SR. After thorough investigation, this study amassed a total of 216 sets of data for the training and testing sets. The ratio between the training and testing sets was established at 8:2, with the initial 173 groups designated as training samples and the final 43 groups allocated for testing.…”
Section: Raw Data Processingmentioning
confidence: 99%
“…DCS of rocks was determined using Hopkinson separated compression rods, with confining pressure gradients of 0, 2, 5, and 10 MPa, and an impact pressure range of 0.2 to 0.6 MPa. This paper conducted intelligent prediction research based on ten influencing factors affecting the DCS of rocks under freeze-thaw cycles [28,[47][48][49][50][51] , including FTC, CP, IP, DD, NWC, WA, ADW, P, PWV, and SR. After thorough investigation, this study amassed a total of 216 sets of data for the training and testing sets. The ratio between the training and testing sets was established at 8:2, with the initial 173 groups designated as training samples and the final 43 groups allocated for testing.…”
Section: Raw Data Processingmentioning
confidence: 99%
“…Li et al [ 3 ] performed uniaxial compression tests on granite with freeze-thaw cycles, and found that the mass of granite increased and the uniaxial compressive strength decreased after freeze-thaw cycles. Mei et al [ 4 ] studied the static and dynamic mechanical properties of freeze-thaw eroded red sandstone using uniaxial compression and Hopkinson pressure bar tests, and concluded that the static and dynamic strengths of freeze-thawed specimens were significantly lower than those of unfreeze-thawed ones. The physical and mechanical parameters of rocks can directly reflect the failure degree of freeze-thawed rocks, but if the change of physical and mechanical properties is the only consideration, the process of rock failure would be ignored.…”
Section: Introductionmentioning
confidence: 99%